2011
DOI: 10.1103/physrevlett.107.233401
|View full text |Cite
|
Sign up to set email alerts
|

Spin and Orbital Magnetic Moments of Free Nanoparticles

Abstract: The determination of spin and orbital magnetic moments from the free atom to the bulk phase is an intriguing challenge for nanoscience, in particular, since most magnetic recording materials are based on nanostructures. We present temperature-dependent x-ray magnetic circular dichroism measurements of free Co clusters (N=8-22) from which the intrinsic spin and orbital magnetic moments of noninteracting magnetic nanoparticles have been deduced. An exceptionally strong enhancement of the orbital moment is verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
101
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 35 publications
7
101
1
4
Order By: Relevance
“…In a previous XMCD study of size-selected cobalt cluster ions by Peredkov et al 52 , decoupling of the spin and orbital angular momenta has been postulated, because the authors found different Langevin scaling for orbital and spin magnetic moments in their experimental data 52 . Decoupled spin and orbital angular momenta would be surprising as these would not only require significant interatomic orbit-orbit coupling for a total µ L to interact with the magnetic field, but this decoupling would also imply that the interaction of the spin magnetic moment with the applied magnetic field were much stronger than the 3d spin-orbit interaction in the 3d transition elements.…”
Section: E Coupling Of Spin and Orbital Angular Momentamentioning
confidence: 99%
“…In a previous XMCD study of size-selected cobalt cluster ions by Peredkov et al 52 , decoupling of the spin and orbital angular momenta has been postulated, because the authors found different Langevin scaling for orbital and spin magnetic moments in their experimental data 52 . Decoupled spin and orbital angular momenta would be surprising as these would not only require significant interatomic orbit-orbit coupling for a total µ L to interact with the magnetic field, but this decoupling would also imply that the interaction of the spin magnetic moment with the applied magnetic field were much stronger than the 3d spin-orbit interaction in the 3d transition elements.…”
Section: E Coupling Of Spin and Orbital Angular Momentamentioning
confidence: 99%
“…As a result, a detailed knowledge of orbital magnetism is crucial in designing new materials with desired hardness and saturation moments. Most interestingly, recent XMCD experiments [9,10] on transition-metal clusters showed huge orbital moments in comparison with their bulk counterparts. Hence these systems may possess a large magnetic anisotropy energy, which makes them potentially interesting for several technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…We formulate here, using several computational methods, a theory of orbital and spin * L.Peters@science.ru.nl magnetism for these clusters. In particular, we take Co clusters as a test case, because Co atoms possess the largest orbital moments among the transition-metals in all their forms, as clusters [9,10], surfaces [4], and bulk [1].…”
Section: Introductionmentioning
confidence: 99%
“…Core-level photoelectron spectroscopy is a surface sensitive and element specific tool which can be applied to study highly diluted samples such as free and deposited clusters by X-ray photoelectron spectroscopy (XPS), [1][2][3][4][5][6][7][8][9] X-ray absorption spectroscopy (XAS) [10][11][12] , extended X-ray absorption fine structure analysis (EXAFS), 13 grazing-incidence small-angle X-ray scattering (GISAXS), 14 X-ray magnetic circular dichroism (XMCD) [15][16][17] and Auger electron spectroscopy (AES). 18 In particular AES and XPS provide information on the initial and final states such as chemical effects, charge transfer, core-hole screening, core-hole binding energies, and electron correlation including final-state term splitting and on-site electron-electron interaction.…”
Section: Introductionmentioning
confidence: 99%